2020
DOI: 10.1002/jmv.25725
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of coronavirus in tears and conjunctival secretions of patients with SARS‐CoV‐2 infection

Abstract: Objective: This study aimed to assess the presence of novel coronavirus in tears and conjunctival secretions of SARS-CoV-2-infected patients.Methods: A prospective interventional case series study was performed, and 30 confirmed novel coronavirus pneumonia (NCP) patients were selected at the First Affiliated Hospital of Zhejiang University from 26 January 2020 to 9 February 2020. At an interval of 2 to 3 days, tear and conjunctival secretions were collected twice with disposable sampling swabs for reverse-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
1,087
5
91

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,037 publications
(1,214 citation statements)
references
References 13 publications
31
1,087
5
91
Order By: Relevance
“…Consistently, SARS-CoV-2 RNA was also dectected in gastrointestinal tissues from COVID-19 patients [24]. Moreover, SARS-CoV-2 was detected in the tears and conjunctival secretions of covid-19 patients [25]. Meanwhile, a retrospective study based nine pregnant women with COVID-19 had for the first time indicated that the possibility of intrauterine vertical transmission between mothers and infants in the late pregnancy was temporarily excluded [26].…”
Section: From the Perspective Of Route Of Transmissionmentioning
confidence: 85%
“…Consistently, SARS-CoV-2 RNA was also dectected in gastrointestinal tissues from COVID-19 patients [24]. Moreover, SARS-CoV-2 was detected in the tears and conjunctival secretions of covid-19 patients [25]. Meanwhile, a retrospective study based nine pregnant women with COVID-19 had for the first time indicated that the possibility of intrauterine vertical transmission between mothers and infants in the late pregnancy was temporarily excluded [26].…”
Section: From the Perspective Of Route Of Transmissionmentioning
confidence: 85%
“…Close contact is also a source of transmission of SARS-CoV-2. For example, SARS-CoV-2 can be transmitted through direct or indirect contact with mucous membranes in the eyes, mouth or nose [37][38][39] . There is also a possibility of aerosol transmission in a relatively closed environment with continuous exposure to high concentrations of aerosol.…”
Section: Transmission Route Of Sars-cov-2mentioning
confidence: 99%
“…intérêt de la télémédecine dans un contexte de pandémie Alejandra Daruich, 1,2 Daniel Martin, 3 Dominique Bremond-Gignac 1,2 *…”
Section: Ocular Manifestation As First Sign Of Coronavirus Disease 20unclassified